2010
DOI: 10.1002/adma.200902975
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Conjugated Polymers Inside Assembled Solid‐State Devices

Abstract: Soluble precursor polymers are processed and assembled into solid‐state devices and subsequently converted in the devices to conjugated electrochromic materials. This method, termed in situ conversion, requires no rigorous cleaning step for the electrode substrate. It eliminates the use of a costly electrolyte bath during the assembly process. This methodology results in high yields for the resultant conjugated system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 36 publications
0
34
0
Order By: Relevance
“…Conducting polymers, such as those used in organic electronic devices, have many favorable properties, such as a low‐temperature synthesis process, inherent compatibility with plastic substrates, and scalable and low‐cost manufacturing, which make them suitable for wearable gas‐sensing devices . However, the limited optical transparency and environmental instability of nanostructured conducting polymer films are major drawbacks of these compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Conducting polymers, such as those used in organic electronic devices, have many favorable properties, such as a low‐temperature synthesis process, inherent compatibility with plastic substrates, and scalable and low‐cost manufacturing, which make them suitable for wearable gas‐sensing devices . However, the limited optical transparency and environmental instability of nanostructured conducting polymer films are major drawbacks of these compounds.…”
Section: Introductionmentioning
confidence: 99%
“…The electrolyte material must be physically contained within the device, and EC materials are prone to oxidation from the air and sensitive to moisture and other environmental contaminants . The assembly process has been simplified with the development of in situ polymerisation . With this method, all of the materials are combined, the device is sealed, and the EC monomer is electropolymerised within the ECD in one step.…”
Section: Electrochromic Device History and Fundamentalsmentioning
confidence: 99%
“…The maximum conductivity achieved by multiple dipping cycles in PEDOT:PSS was 1.71 S/cm. The precursor polymer was converted at +1.1 V in an electrolyte bath to yield poly(EDOT– b –thiophene– b –EDOT), an EC that changed from blue in the oxidised state to red in the reduced state . To ensure device continuity during deformation events, a stretchable polyurethane‐based electrolyte was utilised in later experiments.…”
Section: Electrochromic Colour‐changing Textiles and Fibresmentioning
confidence: 99%
“…Our work has shown that high conductivities of the underlying conductive fabric are not necessary for electrochromic function and we have also presented unique electrochromic device (ECD) architectures. Further, spandex electrodes prepared by this method having conductivity as low as 0.1 S/cm were shown to be able to electrochemically convert precursor polymers to conjugated, electrochromic materials [12–18]. This opens up the potential for the use of a variety of other conductors in the preparation of similar systems [19–24].…”
Section: Introductionmentioning
confidence: 99%